An Aramaic−Hasaitic bilingual inscription from a monumental tomb at Mleiha, Sharjah, UAE. (May 2016) - Overlaet, Bruno; Macdonald, Michael; Stein, Peter
Abstract : Excavations of a monumental tomb in Area F at Mleiha have revealed a lime‐plaster funerary stele with an Aramaic and Hasaitic inscription. The excavation of the tomb was not completed but a preliminary report on the tomb and a discussion of the text is presented. The inscription states that the tomb was built by the deceased's son and mentions the date and his name, family lineage and function in the service of the King of ʿUmān.